ANALISIS FRAMING ROBERT ENTMANT DALAM DETIK.COM DAN RADARBOGOR.ID TENTANG BERITA KECURANGAN PPDB SISTEM ZONASI DI KOTA BOGOR - Wibowo, Faisal; Abdul Mugni, Egi (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2023)
This research aims to analyze the framing of news articles on the case of cheating in the New Student Admission (PPDB) System in Bogor City, using the Robert Entman framing model. The study focuses on the news coverage of Detik.com and Radarbogor.id, with a qualitative approach and a framing analysis method. The data collection technique used was documentation, and the data validity was tested through source and theory triangulation. The analysis was based on the four elements of the Robert Entman framing model: define problems, diagnose causes, make moral judgments, and treatment recommendations. The research findings are as follows: 1). There is a pattern of framing in the news coverage of the cheating case in the PPDB zoning system in Bogor City on Detik.com and Radarbogor.id. 2). The news articles on Detik.com show the firmness of Bogor Mayor Bima Arya in addressing the cheating. 3). The news articles on Radarbogor.id depict the process of the cheating case in the PPDB zoning system in Bogor City.